Efficacy and Safety of Major Antihypertensive Drug Classes in Adults with Hypertension: A Systematic Review - Amar M. Raval; Aryan Rakesh Verma; Dhruva Shaileshbhai Prajapati (Asian Journal of Pharmaceutical Research and Development, 2026)
Background: Hypertension (HTN) remained a major global health concern and a leading risk factor for cardiovascular morbidity and mortality, with many patients requiring more than single-drug therapy to achieve optimal blood pressure control. Objective: This study aimed to evaluate and compare the efficacy and safety of commonly used antihypertensive drug classes, with a focus on different combination therapy strategies. Methods: A systematic review was conducted using PubMed and Google Scholar to identify relevant clinical trials and supporting studies in adult patients with HTN. Studies were selected based on predefined eligibility criteria using the Population, Intervention, Comparison, Outcome (PICO) framework. Data extraction included systolic blood pressure (SBP), diastolic blood pressure (DBP), overall blood pressure control, nighttime blood pressure control, sustained effects, and safety outcomes such as adverse effects, electrolyte changes, and heart rate (HR). A structured comparative approach was used to analyze monotherapy, dual therapy, and multi-drug combinations. Results: The included studies showed that all major antihypertensive drug classes contributed to reductions in SBP and DBP; however, combination therapy demonstrated more consistent and effective overall blood pressure control compared to monotherapy. Differences were observed among drug classes in terms of specific effects, including HR reduction and electrolyte changes. Conclusion: The findings suggested that combination therapy played an important role in achieving better blood pressure control, and a structured comparison of different drug classes and their combinations provided a clearer understanding of their relative efficacy and safety.